(untitled) (Economics and region, 2024)
The article considers the advantages of implementing a compliance-oriented approach to improving the corporate culture of JSC ‘Poltavaoblenergo’ in the context of managing strategic changes of the company. The results of the expert quantitative and qualitative assessment of the corporate culture of JSC ‘Poltavaoblenergo’ are presented. It has been established that the current corporate culture of JSC ‘Poltavaoblenergo’ is characterised by a pronounced dominance of the hierarchical type of culture with clearly formalised and structured workplaces. The work of hired personnel is managed by means of formalised procedures. The article compares the features of the dominant types of corporate culture in the current and desired profiles of the company’s culture. Alternative measures for the formation of corporate culture, which will facilitate the implementation and realisation of strategic changes of JSC ‘Poltavaoblenergo’, are proposed. It is concluded that the improvement of the existing corporate culture of JSC ‘Poltavaoblenergo’ in the context of its contribution to the implementation of these tasks should begin with each employee, and this culture should be humanistic and responsible in its principles.